ROLE OF ART AND MUSIC IN RELIEVING STRESS, DURING AND AFTER COVID-19’s LOCKDOWN: कोविड-19 लॉकडाउन और उसके पष्चात तनाव दूर करने में कला और संगीत को भूमिका - Gupta, Dr. Sunita (International Journal of Research -GRANTHAALAYAH, 2022)
Indian art presents in the form of art from the science of the body to the science of every corpus of the mind, from earth to sky, north to south, east to west, and from Kashmir to Kanyakumari as the subject of its stream of thought. Is. Animals, vegetation, sound, mind, mind, intellect, earth, space, sky, constellations, oceans, rivers, mountains, mountains, animals, birds, forests are all contained in Indian paintings. The artist and musician feels the beauty and sound of nature in every particle of the world through emotions and imagination. Trying to see each side from a new perspective, presents it. Art and music are the sumptuous expressions of the artist’s feelings and perceptions. The purpose of this expression is to provide joy, to create good feelings in life, to remove social problems and sufferings and to lead human beings on the best and inspired path through rasaic artefacts. भारतीय कला षरीर के विज्ञान से लेकर मन के प्रत्येक कोष के विज्ञान को, पृथ्वी से लेकर आसमान को, उŸार से दक्षिण दिषा को, पूर्व से पष्चिम दिषा को, तथा कष्मीर से लेकर कन्याकुमारी को अपनी चिंतन धारा का विशय बनाकर कला रूप में प्रस्तुत करती है। प्राणी, वनस्पति, ध्वनि, मन्, चिक्त, बुद्धि, पृथ्वी, अंतरिक्ष, आकाष, नक्षत्र, बह्याण्ड, नदियां, पर्वत, पहाड़ पषु-पक्षी, वन सभी कुछ भारतीय चित्रों में समाहित है। प्रकृति के कण-कण में व्याप्त सौदर्य और नाद की अनुभूति कलाकार और संगीतकार संवेगो और कल्पना से करता है। प्रत्येक पक्ष को नये-नये आयामों से देखने का प्रयास कर प्रस्तुत करता है। कला और संगीत कलाकार के भावों और बोधों की सरस अभिव्यक्ति है। इस अभिव्यक्ति का उद्देष्य आनन्द प्रदान करना, जीवन में षुभ भावों का उदय करना, सामाजिक समस्याओं और कश्टों का निवारण और रसात्मक कलाकृतियों के माध्यम से मानव को श्रेश्ठ और प्रेरित मार्ग पर अग्रसर करना है।